LITERATURE REVIEW: PENGARUH SLEEP HYGIENE PRACTICE TERHADAP PENINGKATAN KUALITAS TIDUR PADA LANSIA - Puspita, Asih Purwandari Wahyoe; Fauziyah, Afro Salma; Amalia, Anggi Rojiah; Ahdiah, Danies Laelatul; Sabila, Fanny Fauziyyah; Bone, Maharani Pooja Natasya; Robani, Nida Nabila; Puspitasari, Nur Fatimah; Dewi, Prischa Amelliana; Gumilar, Risya Aisyah; Mu’minah, Siti; Suparto, Tirta Adikusuma; Nurhaliza, Rizkia Sukma (Journal Healthcare Education, 2025)
Introduction: Elderly people often experience sleep disorders that affect their physical and mental well-being. This decline in sleep quality is a common problem as we age. Sleep hygiene, as a non-pharmacological approach, focuses on behavioral and environmental changes to improve sleep quality. Aim: to conduct a systematic review to examine the effect of sleep hygiene activities on sleep quality in the elderly. Methods: The search was conducted using several databases including Google Scholar, Research Gate, Pubmed, and Science Direct from the past 4 years, namely 2020 to 2024. The keywords used were "Sleep hygiene", "Sleep Quality / Kualitas Tidur", "Elderly / Lansia", "Eldelry AND sleep hygiene AND improving sleep quality" and a search for Indonesian language articles with the keywords "Lansia AND sleep hygiene AND improving sleep quality" so that 10 articles were obtained for review. Of the 10 articles that met the inclusion criteria, all articles used different sampling methods and techniques. Most studies use probability sampling techniques. The research instrument used in 10 articles and journals to measure sleep quality mostly uses PSQI or Pittsburgh sleep quality index. Results: reviewed from the study of ten articles showed that sleep hygiene significantly improves sleep quality in the elderly. The presence of significant changes in various aspects of sleep quality (sleep efficiency, sleep time, use of sleeping pills, and sleep disturbances) indicates that sleep hygiene can be an effective strategy to overcome sleep problems in the elderly group. The decrease in the prevalence of sleep disorders after the intervention also strengthens the evidence that sleep hygiene has a positive effect. Conclusion: Sleep hygiene has been shown to be an effective approach to improving the sleep quality of older adults. Educational interventions on sleep hygiene can have a positive impact on the sleep patterns of the elderly, thereby improving their overall quality of life. Therefore, the implementation of sleep hygiene needs to be further enforced especially among the elderly to overcome the problem of sleep disorders that often occur.